The role of oxide-scale microtexture on tribological behaviour in the nanoparticle lubrication of hot rolling. (January 2016) - Yu, Xianglong; Jiang, Zhengyi; Zhao, Jingwei; Wei, Dongbin; Zhou, Ji; Zhou, Cunlong; Huang, Qingxue
Abstract: Electron backscatter diffraction (EBSD) of the microtexture in the tertiary oxide scale after hot rolling were investigated. The surface asperity flattening and grain refinement of Fe3 O4 were produced at a thickness reduction of 28% and a cooling rate of 28 °C/s. Microtexture development of Fe3 O4 manifests as a strong θ fibre parallel to oxide growth, including the {100}<001> and {001}<110> textured components, whereas the {0001}<10 1 ̅ 0> component dominates in α -Fe2 O3 as the favoured basal slip. The tribological effect of α -Fe2 O3 at the contact surface of steel and rolls was considered at low and high thickness reductions. The propagation of cracks along the Fe3 O4 grain boundaries could create a dish to collect nanoparticles during lubrication and thereby changed the wear rates. Highlights: Evolutions of microtexture in tertiary oxide scale are investigated. Surface asperity flattening is pronounced at high thickness reduction of 28%. Magnetite has {100}<001> and {001}<110> texture components. { 0001 } < 10 1 ¯ > component dominates in α -Fe2 O3 . Nanoparticles can be trapped in the cracks to change the wear rates.